Estudo de caso sobre exposição a violência intrafamiliar de uma criança PAEE - Pereira, Juliana Maschio (Universidade Federal de São Carlos, 2017)
The present work describes a case study with the objective of investigating the impact of intrafamily violence on the academic performance of children in the target group of special education considering the conditions of children with disabilities exposed to this context of violence. The participants were a child with disabilities in school, his mother and the teacher of the regular classroom of the school he attended. The results showed the low quality of family relationships and the impact on the child's academic life. It was concluded that the low quality of interactions in the family environment can be aggravating for the learning of the target audience of special education.
Case study on exposure to intrafamily violence of a PAEE child
Keywords: Educação Especial; Violência intrafamiliar; Criança PAEE; Special education; Intrafamilial violence; Target special education children; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA